Outcomes and predictors of survival in blast phase myeloproliferative neoplasms. (July 2018) - Lancman, Guido; Brunner, Andrew; Hoffman, Ronald; Mascarenhas, John; Hobbs, Gabriela
Highlights: Median overall survival after diagnosis of MPN in blast phase was 5.8 months. Long-term survival was achieved with allogeneic stem cell transplantation. RBC transfusion dependence portended a poor outcome after transplantation. Patients receiving hypomethylating agents had a median survival of 6.7 months. Patients receiving supportive care had a median survival of just 1.1 months. Abstract: We retrospectively reviewed treatment outcomes for 57 patients with myeloproliferative neoplasms in blast phase (MPN-BP). The median overall survival (OS) of the entire cohort was 5.8 months. For patients receiving induction therapy, 67% achieved a complete response (CR) and 75% received stem cell transplantation (SCT). Median OS for all transplanted patients (n = 19) was not reached after a median follow-up of 19.2 months compared with 3.8 months in non-transplanted patients (p < 0.0001); patients who did not receive SCT after induction chemotherapy survived a median of 4.9 months. OS was not improved in patients transplanted after CR (OS not reached after median follow-up of 26.7 months) compared with those transplanted upfront or after suboptimal response to initial therapy (9.0 months; p = .097). Those who were transfusion-dependent during their MPN course and received SCT had a median OS of 4.4 months, with all patients dying from SCT complications. Patients receiving hypomethylating agents (HMA) survived 6.7 months, while those receiving supportive care survived 1.1 months. Although outcomes for MPN-BP remain poor, long-term survival can be achieved in appropriately selected patients utilizing SCT, optimally after attaining a complete response with induction therapy. For patients ineligible for SCT, HMAs can offer similar survival to induction chemotherapy with less toxicity.